Kekerasan Simbolik Melalui Dominasi Modal Agama pada Sekolah Swasta di Kabupaten Bantaeng - Suardi (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2021)
Disparities between private school students and public school students are common because of differences in the accumulation of economic, social, cultural, symbolic and religious capital. This article aims to analyze and find the existence of religious capital as a form of capital accumulation to overcome symbolic violence. This research was conducted using the mixed method concurrent embedded method in 10 private schools and 6 public schools. Qualitative research informants as many as 43 people were determined using purposive sampling while 301 quantitative research respondents were determined using random sampling. Data was collected using a Likert and Gutman scale questionnaire, direct observation sheets, structured interview sheets and documents. The qualitative data that has been collected is analyzed through the stages of data reduction, displaying the data and then drawing conclusions, while the quantitative data is analyzed through the stages of verification, tabulation and data percentage. The results of the study show that religious capital is the dominant thing owned by private schools which can be optimized to seize dominance in the realm of education so that students do not experience symbolic violence. The forms of social capital owned by private schools are (i) public trust in private schools in providing religious learning, character or social values, with a percentage of 71.77 percent, (ii) spiritual leadership which is always dominated by private school actors in various fields. religious activities, with a percentage of 83.05 percent.